Clinicopathological Relationships in an Aged Case of DOORS Syndrome With a p.Arg506X Mutation in the ATP6V1B2 Gene - Zádori, Dénes; Szalárdy, Levente; Reisz, Zita; Kovacs, Gabor G.; Maszlag-Török, Rita; Ajeawung, Norbert F.; Vécsei, László; Campeau, Philippe M.; Klivényi, Péter (Frontiers in Neurology, 2020)
DOORS (deafness, onychodystrophy, osteodystrophy, intellectual disability (mental retardation), and seizures) syndrome can be caused by mutations in the TBC1D24 and ATP6V1B2 genes, both of which are involved in endolysosomal function. Because of its extreme rarity, to date, no detailed neuropathological assessment has been performed to establish clinicopathological relationships and, thereby, understand better the neurobiology of this disease in aged cases. Accordingly, the aim of the current study was to highlight the clinicopathological characteristics of a novel case with a presumable de novo mutation in the ATP6V1B2 gene from a neuropathological point of view. This Caucasian male patient, who died at the age of 72 years, presented all the typical cardinal signs of DOORS syndrome. In addition, behavioral alterations, pyramidal signs, and Parkinsonism were observed. The p.R506X pathogenic mutation identified in the ATP6V1B2 gene was responsible for the clinical phenotype. The detailed neuropathological assessment revealed a limbic-predominant tauopathy in the forms of argyrophilic grain disease, primary age-related tauopathy, and age-related tau-astrogliopathy. In summary, we present the first detailed clinicopathological report of a patient with DOORS syndrome harboring a pathogenic mutation in the ATP6V1B2 gene. The demonstrated tauopathy may be considered as a consequence of lysosomal and/or mitochondrial dysfunction, similar to that found in Niemann–Pick type C disease, which is another lysosomal disorder characterized by premature neurodegenerative disorder.